Incidental Benign Metastasizing Leiomyoma in a Patient with Bone Sarcoma: A Case Report - Zanndor Jacob del Real-Romo; Carlos Montero-Cantú; Oscar Villegas-Cabello; José Antonio Díaz-Elizondo; Danae Reyes-Salas; Rene Palomo-Hoil; Guillermo Peralta-Castillo; David Martínez-Sánchez; Eduardo Flores-Villalba (Case Reports in Surgery)
Background. The benign metastasizing leiomyoma is an exceptionally rare entity; it presents with ectopic leiomyoma nodules with a benign pattern. Symptoms vary according to the anatomic location. The diagnosis is histopathological, usually in patients with history of hysterectomy. Case Presentation. A 36-year-old female with 2-month history of left knee pain was diagnosed with bone fibrosarcoma. A CT scan showed pulmonary nodules. The patient started neoadjuvant chemotherapy. Conservative surgery of pelvic limb was achieved. A new CT scan reported pulmonary nodules that remained in relation to the previous CT. A nodule resection by thoracotomy and TOB (transoperative biopsy) was performed. The final pathology report described benign proliferative lesions consistent with benign metastatic leiomyoma. Conclusions. Benign metastatic leiomyoma is a rare condition presenting with uterine and extrauterine nodules most commonly in the lung. The diagnosis is histopathological. The surgical procedure must be reserved for selected patients.